Petrogenesis of two stages of Cretaceous granites in south‐west Fujian Province: Implications for the tectonic transition of South‐east China. (5th March 2018) - Zhao, Xilin; Yu, Shengyao; Jiang, Yang; Mao, Jianren; Yu, Minggang; Chen, Zhihong; Xing, Guangfu
Abstract : Zircon U–Pb data indicate that Cretaceous magmatism in Fujian Province occurred in two pulses, with the Xiyang, Yangshan, Wuci, Dehua, Juzhou, and Xiandu plutons emplaced between 147 ± 1 and 126 ± 1 Ma and the Hutou and Guangqiao plutons emplaced at 109 ± 1 Ma. Combining these previously published ages with the new data obtained during this study indicates that the magmatism in the study area occurred in two distinct stages at 145–125 and 110–100 Ma, both have I‐type characteristics. The earlier I‐type granites are characterized by relatively high concentrations of SiO2 (mean = 75.73 wt.%) and low concentrations of MgO (mean of 0.21 wt.%) and are metaluminous to weakly peraluminous (mean A/CNK = 1.03). They contain relatively high total rare‐earth element (ΣREE) concentrations (mean of 139.3 ppm) with well‐developed Eu anomalies and are relatively enriched in the large‐ion lithophile elements (LILE) and the light REE (LREE) but depleted in Ba, Sr, P, Ti, Nb, and Ta. In contrast, the younger I‐type granites contain lower concentrations of SiO2 (mean of 67.63 wt.%), higher concentrations of MgO (mean of 1.47 wt.%), and are metaluminous to weakly peraluminous (mean A/CNK = 0.96). They also have moderate REE values (mean of 150.26 ppm) without significant Eu anomalies and are relatively enriched in LREE, Rb, Th, U, K, Sr, and Pb and depleted in Nb, Ta, P, Ti, Y, and Yb. The two‐stage Nd model ages (T2DM ) of Cretaceous granites are 1.46 to 1.88 Ga (mean of 1.57 Ga) and 1.16–1.60 Ga (mean of 1.36 Ga), respectively. The two‐stage Hf model ages (T2DM ) of Cretaceous granites are 1.19–1.82 Ga (mean of 1.54 Ga) and 0.46–1.20 Ga (mean of 0.91 Ga), respectively. It is likely that the earlier I‐type granites were derived from magmas generated by the partial melting of Mesoproterozoic metabasaltic material, whereas the later I‐type granites were derived from magmas generated by partial melting of a mixed lithology containing Mesoproterozoic to Neoproterozoic metabasaltic to metatonalitic rocks that were underplated by medium‐ to high‐K basaltic magmas. A geological comparison between south‐western Fujian Province and adjacent areas indicates that the earlier I‐type granites were emplaced in a compressional environment associated with the subduction of the paleo‐Pacific Plate at 145–125 Ma. In contrast, the later I‐type plutons are associated with intraplate extension accompanied by the post‐subduction slab roll‐back of the paleo‐Pacific Plate. The two magmatic stages represent a transition from compressional to intraplate extensional tectonics between 125 and 110 Ma, with mantle‐derived material playing a crucial role in the formation of the I‐type granites.